(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This research deals with the analysis of drought and humidity periods in Lattakia Governorate - northwest Syria - and studying their spatial and temporal distribution by applying the Standardized Precipitation Index (SPI) to rainfall data for eight main stations between the years (1993-2023) during the time periods (3-6) months، in addition to calculating the recurrence rates of drought periods according to the SPI index. Then، digital maps were prepared using the GIS program to show the rates of drought severity and recurrence. The results showed that the stations of Slenfeh and Kassab witnessed local drought during a period of 6 months، ranging between 10% - 25%، while the drought was not of a high degree in the other stations and its percentage was less than 10%. It was found that the 6-month period is the most appropriate for the research area as it gave a clearer picture of the changes in rainfall during the rainy months.